Increasing the Role of Private Sector in Development Opportunities in Africa using Innovative Finance Principles - Ndlovu, Loyiso (Graduate School of Business (GSB), 2019)
This research examines the role of Development Financing Institutions given the increasing scale of the development needs with the advent of the SDGs. It asks how DFIs should be reviewing their role, using Innovative Finance tools and bringing on board more private sector partners into Development to achieve greater development outcomes. This qualitative study examines 82 DFIs across the African continent using secondary data from surveys and speeches referencing Innovative Finance for DFIs. The research theory is developed by applying Grounded Theory in order to develop a theory which can be used to frame the logic for increasing engagements with private sector partners. Bottom-up secondary data is utilised to develop a DFI Engagement model for making strategic choices on private sector partnerships. The data was coded for analysis with eight different coding frames for the development of data categories to inform the key themes that support the theory. The results showed that generally DFIs across the African continent are potentially missing out on opportunities for greater development through lack of external engagement in particular private sector. In addition, their use of Innovative Finance tools is limited by awareness and technical capability. The research proposes how best the private sector should be engaged through the engagement framework, and recommends potential new roles for DFIs to play in this rapidly changing landscape. Lastly recommendations are made on further areas of work for the DFI fraternity to institutionalise such recommendations.